The burden of unexpected costs in medical school. - Madeleine Ball; LeAnn Lam; Megan Tigue; Simone Herzberg; Luke Finck (PLoS ONE)
Background The cost of medical school continues to climb. What has yet to be well-understood are the so-called "unexpected costs" of medical school that, while not explicitly required, are considered paramount to success. This study aims to identify, quantify, and analyze the impacts of these costs of medical school and offer suggestions in alleviating these burdens. Methods Medical students across the United States were administered a questionnaire inquiring about the unexpected costs of medical school including test prep materials, clinical supplies, student fees, and the impact of these costs on mental and financial health. In this multi-institutional, cross-sectional survey study, outcomes included total cost, perception of expected vs. actual cost, and impact on well-being. Results From January to June 2022, 499 survey responses were collected. The average total additional costs were $4,937, with 83% of respondents stating they spent more during medical school than expected. 51% reported their institutions' cost of attendance did not accurately predict expenses. These costs were a financial constraint for 68% of students, with a significant increase in constraint for first-generation college students (89% vs 65%, p = 0.02). Financial concerns impacted 65% of students' mental health and well-being during their medical career, with a significantly increased impact on first-generation college students (85% vs 62%, p = 0.045). Conclusions Most students believed the total cost of medical school was significantly more than expected, serving as a source of stress and negatively impacting their mental health. The financial constraints and impact on mental health and well-being were most pronounced for first-generation college students. This study illuminates the importance of improving communication regarding costs outside of tuition and providing support and advocacy to alleviate those costs. Future investigation should further examine how other demographics are impacted by the burden of unexpected costs in medical school.